Multi-layer anodes for high-current applications. (20th January 2023) - Hamedi, Amir-Sina; Yao, Adrian; Martin, Roxana; Roig, Raymundo; Valadez, Michael Rivas; Pile, Donald; Shellikeri, Annadanesh; Liu, Baichuan; Wheeler, Dean R.
Abstract: In this work, we present a combination of experiments and modeling of a two-layer anode structure designed by EnPower Inc. for high-energy and fast-charge capabilities. The anode consists of lower porosity near the current collector and higher porosity near the separator with comparable active materials in both regions. A pseudo-two-dimensional electrochemical–thermal model was designed to represent the performance of this electrode. Simulations, consistent with experiments, show superior ion transport and lithiation in the multi-layer anode (MLA) compared to a conventional single-layer anode (SLA). Surprisingly, this improved transport in MLA manifests as enhanced cathode performance during high-rate discharge and this, in turn, provides higher energy density for MLA. Similarly, during fast charge, less irreversible lithium is deposited due to this improved transport in MLA, and hence MLA exhibits less capacity fade compared to SLA. Polarization analysis demonstrates marginally lower cumulative overpotential for MLA in different case studies; however, MLA cells maintain a significantly higher capacity in the same conditions and have more than double the cycle life. This means despite the apparently limited polarization benefit provided by MLA; the MLA structure can more reliably be employed in cell designs. Additional design changes are also analyzed by means of the model.